If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + 3 + -5y = 5 + y + -5 Reorder the terms: 3 + 7y + -5y = 5 + y + -5 Combine like terms: 7y + -5y = 2y 3 + 2y = 5 + y + -5 Reorder the terms: 3 + 2y = 5 + -5 + y Combine like terms: 5 + -5 = 0 3 + 2y = 0 + y 3 + 2y = y Solving 3 + 2y = y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 3 + 2y + -1y = y + -1y Combine like terms: 2y + -1y = 1y 3 + 1y = y + -1y Combine like terms: y + -1y = 0 3 + 1y = 0 Add '-3' to each side of the equation. 3 + -3 + 1y = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 1y = 0 + -3 1y = 0 + -3 Combine like terms: 0 + -3 = -3 1y = -3 Divide each side by '1'. y = -3 Simplifying y = -3
| 4x^2-32x=-14 | | 4x^2-32x=-24 | | -8x+10=8-4x-5x | | 3y-5=4y-3 | | 11-2(a-1)=4a+a | | -37+-56= | | 2x/4=7 | | F(x)=3+ln(x) | | 2(2x+1)=5x-9x | | 7x+7=12x+7 | | 17x-6=14x-9 | | -25z-0.1=-35z+1.3 | | 10+18=-4(2x-7) | | 4x+5=9x+25 | | 3.3+x=5 | | x^2+y^2+z=27 | | 9-3(4y+6)=0 | | X+24=9x+56 | | 8=x(x-2) | | X-6=46 | | x/2-314=123 | | 10x-1447=933 | | -7+7=25 | | -10(s+3)=-13 | | cos(40)=x/14 | | 2y+5-1=15 | | 4(4s+4)=96 | | 7(2l+1)=77 | | 2(a-6)=34 | | (u-6)*10=100 | | 5/12x-3/4(x-3)=1/6(2x-7) | | sin^2x/1-cosx |